Social Environment Ameliorates Behavioral and Immune Impairments in Tyrosine Hydroxylase Haploinsufficient Female Mice - Garrido, A.; Cruces, J.; Ceprián, N.; Hernández-Sánchez, C.; De Pablo, F.; De la Fuente, Mónica (Journal of neuroimmune pharmacology, 2021)
The social environment can influence the functional capacity of nervous and immune systems, and consequently the state of health, especially in aged individuals. Adult female tyrosine hydroxylase haploinsufficient (TH-HZ) mice exhibit behavioral impairments, premature immunosenescence and oxidative- inflammatory stress. All these deteriorations are associated with a lower lifespan than wild type (WT) counterparts. The aim was to analyze whether the cohabitation with WT animals could revert or at least ameliorate the deterioration in the nervous and immune systems that female TH-HZ mice show at adult age. Female TH-HZ and WT mice at age of 3–4 weeks were divided into following groups: control TH-HZ (5 TH-HZ mice in the cage; TH-HZ100%), control WT (5 WT mice in the cage; WT100%), TH-HZ > 50% and WT < 50% (5 TH-HZ with 2 WT mice in each cage) as well as TH-HZ < 50% and WT > 50% (2 TH-HZ and 5 WT mice in each cage). At the age of 37–38 weeks, all mice were submitted to a battery of behavioral tests, evaluating sensorimotor abilities, exploratory capacities and anxiety-like behaviors. Subsequently, peritoneal leukocytes were extracted and several immune functions as well as oxidative and inflammatory stress parameters were analyzed. The results showed that the TH-HZ < 50% group had improved behavioral responses, especially anxiety-like behaviors, and the immunosenescence and oxidative stress of their peritoneal leukocytes were ameliorated. However, WT mice that cohabited with TH-HZ mice presented higher anxiety-like behaviors and deterioration in immune functions and in their inflammatory stress parameters. Thus, this social environment is capable of ameliorating the impairments associated with a haploinsufficiency of the th gene. Graphical Abstract